A field theoretical approach to the Debye-Huckel electrolyte differential capacitance in a slab - di Caprio, D.; Stafiej, J. (Condensed Matter Physics, 2001)
The effective Hamiltonian of our field theoretical model yields the linearized
Debye-H¨uckel theory in the bulk. Here we consider it for a confined geometry
of a slab. The differential capacitance is computed using two ways.
The first relates it to the charge-charge correlation function by calculating
the response to charging of the slab walls. The other relates it to the fluctuation
of charge in one half of the slab. Since the model is exactly soluble
in terms of the diagonal representation we can verify the fact that the two
ways are consistent with each other and with the Gouy-Chapman differential
capacitance in the limit of a thick slab. The interest of this derivation is
to relate a measurable quantity to the structural information contained in
the charge-charge correlation function. Ефективний гамільтоніан нашої теоретико-польової моделі дає лінеаризовану теорію Дебая-Гюкеля для об’ємних властивостей. Тут
ми розглядаємо його для обмеженої геометрії пластини. Диференціальна ємність обчислюється двома способами. Перший пов’язує її
з прямою кореляційною функцією заряд-заряд на основі обчислення відгуку до заряджання стінок пластини. Інші методи пов’язують її
з флуктуацією заряду в одній половині пластини. Оскільки модель є
точно розв’язувана в термінах діагонального представлення, ми можемо перевірити той факт, що два способи узгоджуються між собою
і з виразом для диференційної ємності Гуї-Чепмена в границі тонкої
пластини. Цінність цього висновку мусить пов’язувати вимірювальну
величину зі структурною інформацією, яка міститься в кореляційній
функції заряд-заряд.